Performance Analysis of Terminal II of The New Makassar Container Port in Supporting Logistics Distribution in South Sulawesi - Riska Damayanti; Andi Sitti Chairunnisa; Esther Sanda Manapa; Eliyah A.M Sampetoding; Toong Khuan Chan; Misliah Idrus (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
The New Makassar Container Port serves as logistics hub that impacts local economic growth and facilitates the distribution of goods between regions. To optimise port operations, it is crucial to establish connections with the hinterland area. Terminal II is designed to handle the flow of containers. According to the current stage of development, the existing capacity and facilities should be able to handle a larger volume of containers. This study aims to evaluate the performance of the logistics system through time and service performance indicators. The research method involves both qualitative and quantitative approaches, with freight forwarders and shipping companies as the sample population. The analysis involves a descriptive analysis of the logistics system and an Importance Performance Analysis (IPA) to assess performance and satisfaction of service users. The Potential Gain in Customer Value (PGCV) method was used to determine priority areas for improvement. The results show that Terminal II of the New Makassar Container Port performs well and meets the standards set by the Director General of Sea Transportation. However, international shipping services have not been fully utilized, contributing to low container flow and underutilization of the installed capacity. Additionally, export activities remain heavily reliant on commodities instead of industrial goods. The IPA and PGCV analyses revealed that the priority areas of improvement include sustainable and customer-oriented operating processes, with a conformity rate of 79% and the highest PGCV value of 6.22. Regular evaluations of both the physical and human aspects of port operations are necessary.